Frequency of Pyloric Stenosis in Patients Presenting with Persistent Vomiting - Zabih Ullah, Rania Hidayat, Hafizullah Khan ,Waqar Zulfiqar, Adil Naseer, Shawana Asad (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Pyloric stenosis is an uncommon condition in infants characterized by abnormal thickening of the pylorus muscles in the stomach leading to gastric outlet obstruction. Clinically infants are well at birth. Then, at 3 to 6 weeks of age, the infants present with "projectile" vomiting which can lead to dehydration and weight loss. Objective: To determine the frequency of pyloric stenosis in patient presenting with persistent vomiting. Material and Method: This Cross Sectional Study was conducted in the department of Gastroenterology, ATH, Abbottabad from 5th October 2020 to 5th April 2021. A total of 115 patients of both gender with persistent vomiting for more than 5 days were included in the study. Abdominal ultrasound was done by a consultant gastroenterologist of three years post fellowship experience. Pyloric stenosis was noted. Results: Age range in this study was from 1 to 40 years with mean age of 6.226±6.62 years and mean duration of complaints was 9.869±3.76 days. Male patients were 88.7%% and females were 11.3%%. Pyloric Stenosis was observed in 93% patients. Conclusion: Our study concluded that that pyloric stenosis is 4 times more common in males compared to females and is more common among younger age groups as compared to adult patients. Keywords: Persistent vomiting, pyloric stenosis, Ultrasound, Frequency